DI-094 Treatment of pulmonary emphysema associated with ALPHA-1-antitrypsin deficiency. (24th March 2015) - Llamas, S; El Mahmoud, S; Gutierrez, E; Lopez, D; Castillo, A; Juan, J; Ortiz de Urbina, J; Ortega, L; Medina, J; Ruano, R
Abstract : Background: Alpha-1-antitrypsin deficiency (AATD) is an inherited disorder that predisposes to the development of emphysema. Replacement therapy is an expensive chronic treatment. Purpose: To describe the characteristics of patients diagnosed with AATD and emphysema in our hospital. To follow up their progress using spirometric data and the number of hospitalizations before and after one year of treatment. Material and methods: A retrospective study of the individual progress of patients with AATD who have been treated with replacement therapy. Review of medical records and pharmacy dispensing data. Variables: sex, age at diagnosis, phenotype, FVC, FEV1, FEV1/FVC and number of exacerbations that required hospitalisation before and after treatment. Results: 8 patients received replacement therapy. The average age was 51 ± 10 years. 7 patients had the piZZ deficient phenotype and 1 MM phenotype and null/null genotype. The guideline in all cases was 180 mg/kg every 21 days as an intravenous infusion. AAT values at diagnosis ranged from 9 mg/dL to 82 mg/dL. In 2 patients, the number of hospitalizations was low once the treatment started. In 1 patient the number of hospitalizations increased. The average FEV1 before starting treatment was 1.30 ± 0.19 L and one year after was 1.33 ± 0.48 L, representing an increase of 0.029 L. The average FEV1/FVC prior to treatment was 42.9 ± 8.02 L and 46.15 ± 7.24 L a year after, increasing by 3.26 L after one year of treatment. Conclusion: The objective in AAT replacement therapy is to slow down the progression of emphysema and respiratory functional impairment, reducing severe exacerbations. We might with the results obtained that the treatment is effective because the respiratory parameters in our patients were stable after one year of treatment showing a slight increase, and the number of hospitalisation due to respiratory causes was practically unchanged. However, the limited number of cases and follow-up is insufficient to generalise findings. Larger cohorts are required. Reference: Normativa SEPAR 2006. Arch Bronconeumol 2006;42(12):645–59 No conflict of interest.